Schaum's Fluid Mechanics and Hydraulics Problem 13-81: Lift and Drag on a Flate Plate - Adams, Thom (McGraw-Hill's AccessEngineering., 2013)
This video demonstrates how to determine the forces acting on the signboard at parallel and at a right angle to the wind direction.